PENYITAAN HARTA KEKAYAAN PELAKU TINDAK PIDANA MONEY LAUNDERING DITINJAU DARI WAKTU TERJADINYA TINDAK PIDANA (TEMPUS DELICTI ) (Studi Putusan MARI No.1195/K/PIDSUS/ 2014) - Elfirda Ade Putri; Alvi Syahrin; Muhammad Ekaputra; Chairul Bariah (USU LAW JOURNAL, 2016)
ABSTRACT The Verdict of the Jakarta Pusat District Court No. 38/pidsus/tpic/2013/Pn.Jkt.Pst indicted Luthfi Hasan Ishak for committing money laundering with 18 year-imprisonment. The result of the research showed that the confiscation of the property which came from money laundering criminal act that occurred before tempus delicti could be performed as it was stipulated in Chapter V, part 4 from 38 until Article 46 of the Penal Code, and some part of it stipulated in Chapter XIV on   Confiscation stipulated in Article 1, letter 16 of the Penal Code. The judge’s consideration in his verdict was not contrary to das solen and das sein. In this case, the defendant’s statement could not prove that his property was obtained from LHKPN so that the panel of judges concluded that his property came from corruption criminal act. Judges as part of law enforcement should improve their performance in their verdicts in upholding legal certainty, sense of justice, and benefit. Keywords: Confiscation of Property, Money Laundering, Tempus Delicti